Political Reforms For Regime Survival: Algeria From 1988 To Post-Covid-19 Era - Khelfa, Nouha; Zamani, Sayed Mustafa (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2023)
This study examines how the regime in Algeria could survive the different popular uprisings throughout history, unlike the rest of regimes that experienced the Arab Spring. The study argues that since the foundation of the republic, the Algerian regime has always supported quick political reforms as a survival tactic. Contrary to other Arab dictatorships, the FLN has always been in power, but, as a survival tactic, it has always been willing to make concessions. The Algerian government used immediate political reforms to dictate the populace's behavior during uprisings, which over time created a kind of negative reinforcement. The study will employ an extensive literature review and archival records to support this argument. Relying on a fusion of classical conditioning, power-maximization theory and inherent factors approach, this study will prove that political reforms are used mostly as a tool of regime survival and power maximization.